PENGEMBANGAN BUDAYA PENCAK SILAT SEBAGAI ATRAKSI PARIWISATA BUDAYA DI INDONESIA (STUDI PADA PERGURUAN PENCAK SILAT MERPATI PUTIH) - Elang Kusumo; Diena Mutiara Lemy (Jurnal Pariwisata Pesona, 2021)
Traditional Indonesian martial art called Pencak Silat , as one of the nation's cultural assets, pencak silat is increasingly developing in Indonesian society, both from the sports and from the socio-cultural. The purposed of this research was conducted to determine the potential development of pencak silat at Merpati Putih as a cultural tourism attraction. The research was conducted on active and passive members (who had been members) of the Merpati Putih Pencak Silat  (with total 612 of respondents). pencak silat  “Merpati Putih” (known as PPS Betako Merpati Putih) was formed around the 1550s BC. This research used a qualitative descriptive method, with primary data from the results of the questionnaire, and enriched with secondary data obtained from the internet and several other sources to complement this research. This research used a qualitative descriptive method, explaining the situation and facts found in the field. To explore members' perceptions of the potential development of pencak silat “Merpati Putih” as a cultural tourism attraction, questionnaires, online observations and interview conducted on the members of PPS Betako Merpati Putih. Pencak silat “Merpati Putih” has the potential to be developed as a cultural tourism attraction, by developing and managing it more professional so that it becomes a cultural tourism asset in term of tourists interest.